Mercury in soil and attic dust as a reflection of Idrija mining and mineralization (Slovenia) - Gosar, Mateja; Šajn, Robert (Geologija, 2001)
In Idrija and its close surroundings the influence of natural dispersion of mercury and of half-a-millenium mining on the environment have been studied. By sampling (69 soil and 65 attic dust samples) of a 51 km2 area it was established that on 17.4 km2 Hg concentrations in soil exceed the critical values for soil (10 mg/kg). The estimated mercury mean for the studied area is 8.6 mg/kg (0.42 - 973 mg/kg) for soil and 43.5 mg/kg (1.8 - 1055 mg/kg) for attic dust. The Hg concentrations in attic dust are on an average 3.6 times higher than in soil. The highest ratios between Hg abundances in dust versus soil were found in the most distant localities and on higher altitudes above the sea level. Hg in soil exceeds Hg in attic dust only in localities in which the source of the metal is rock next to atmospheric emission. The spatial Hg distribution in soil and attic dust correlate well (r=0.87) and depends very much upon morphology of terrain. High values occur in the Idrijca river valley and at base of slopes, while lower values prevail at higher elevations and at margins of the investigated area.